Nyantri Jaman Now :Manifestation of Indonesian Santri Identity in the Digital Era - Puri Septiana Nursetiyawati; Arizal Mutahir; Laila Sabrina (Jurnal Studi Agama)
This article examines the phenomenon of nyantri (studying at pesantren) in the digital era as a manifestation of cultural and religious identity in the context of rapid social change. The purpose of this research is to understand the function of nyantri as a means of preserving and shaping personal and social identity amidst the currents of globalization and the development of digital technology. This research also aims to identify and analyze the personal and social identities of students in the digital era. The method used in this research is descriptive qualitative with in-depth interview techniques and participatory observation at Pondok Pesantren Al Ikhsan Beji, Banyumas, Central Java. The research results show that although the pesantren have adapted to technological developments, traditional values remain the main foundation in the process of education and character formation of the students. Students utilize social media and technology to broaden their religious horizons, while still maintaining conventional religious practices. The digital era brings challenges for students in managing change, but it also opens up space for innovation in showcasing their identity. In the digital era, being a student remains relevant as a means of forming a strong identity, despite shifts in the methods and practices used